'The message is the medium': Evaluating the use of visual images to provoke engagement and active learning in politics and international relations lectures*. (May 2018) - Roberts, David
Globalization and digitization have combined to create a 'pictorial turn' that has transformed communication landscapes. Routine exposure to visual stimuli like images has acculturated our students' learning processes long before their arrival at university. But when they reach us, we expose them to text-centric teaching out of kilter with the worlds from which they come. More importantly, emerging scholarship argues that such textual hegemony is out of kilter with how they learn. This article describes a 3-year experiment to assess the veracity of such claims. It found that student academic engagement was greater when apposite images were applied. In addition, the experiment revealed that introducing imagery triggered active learning behaviours. The article concludes with a discussion of the implications of these findings for politics and international relations teaching.